Setting Up New Standards: A Preview of Indonesias New Competence-Based Curriculum - Helena I.R. Agustien (TEFLIN Journal: A publication on the teaching and learning of English, 2004)
This paper aims at describing some theoretical foundations as well as practical considerations underlying the new competence-based curriculum. First, a pedagogically motivated model of communicative competence (CC) suggested by Celce-Murcia et al. (1995) is discussed. Second, a systemic functional view regarding the relations between text, context of situation and context of culture (Halliday 1985) relevant to the production of various genres is also a central issue. Third, literacy levels - performative, functional, informational, epistemic (Wells 1991) - have also been taken into considerations. Fourth, the curriculum regards meanings as its top priority and, metafunctions (Halliday 1978) are of primary importance. Finally, similarities and differences of spoken and written language (Halliday 1986) that tend to be overlooked in the previous/existing curricula are now illuminated.